Development of a Thermoluminescence - Radioluminescence Spectrometer - França, Leonardo Vinícius da Silva (2018)
In this work, initially the radioluminescence (RL) and thermoluminescence (TL) techniques are presented. The radioluminescence is the prompt luminescence emitted by a material under ionizing radiation exposure. The thermoluminescence is the luminescence emitted by a material previously exposed to ionizing radiation when excited by heat. Enegy bands concepts, defects in crystals and the different processes of ionization that take place in matter when exposed to ionizing radiation are briefly discussed in order to present the mechanisms involved in RL and TL processes. The usage of the techniques in characterization of materials and dosimetry is reported, legitimating the importance of the instrument developed. Mechanical and structural parts as well as a description of each component of the instrument are fairly described. The implemented algorithm for controlling the instrument and acquiring data is also discussed. The development of the instrument enabled us to generate temperature ramps with a quite good performance, reaching temperatures up to 500 °C with deviations up to 2 °C, having used heating rates between 0.5 °C/s and 5 °C/s. Calibrations of optical spectrometer used in light collection and irradiation system were carried out. Lastly, TL and RL spectra tests were performed. The RL tests were carried out using several materials which emission spectra are well known by literature, namely, carbon-doped aluminium oxide Al2O3:C, terbium-doped gadolinium oxysulphide Gd2O2S:Tb, europium-doped yttrium oxide Y2O3:Eu and dysprosium-doped calcium borate CaB6O10:Dy. For the TL spectra test, the aluminium oxide doped with carbon Al2O3:C was used. The results of RL and TL spectra tests showed a good agreement with the literature, pointing out that the instrument developed in this work is comparable to others instruments in operation from others research groups, making our results reliable.